Dampak Kekerasan Seksual di Ranah Domestik terhadap Perkembangan Remaja - Fita Kumalasari; Ratriana Y. E. Kusumiati (Fakultas Psikologi Universitas Pancasila, 2023)
The protection of children from sexual abuse, both within the family and society, is a fundamental right that must be guaranteed. The phenomenon of domestic sexual violence committed by family members indicates a lack of protection and security for children to grow and develop. The impact of such experiences can be detrimental to a child's development in the present and potentially dangerous in the future. This study aims to comprehensively describe the impact of domestic sexual violence and to discuss inhibiting and supportive factors in the recovery process. A qualitative phenomenological method with an Interpretative Phenomenology Analysis (IPA) approach was used in this study. The researcher conducted semi-structured interviews with an epoche attitude as the basis for answering the research objectives. Participants were purposively selected, and two female participants aged 10-19 years who experienced sexual violence by family members were obtained. The study found that there are psychological impacts that disrupt adolescent development in cognitive, emotional, physical, and social aspects. Additionally, there are post-traumatic symptoms, social factors that worsen the impact of sexual violence, and supportive factors that aid in the recovery process. The study also discovered a new finding: the lack of sexual education and power relations as contributing factors to domestic sexual violence.